Hepatitis E induced severe myositis - Nepali, R; Shah, DS; Sigdel, MR (Journal of Institute of Medicine Nepal, 2016)
Hepatitis E is one of a rare cause of viral myositis in immunocompromised patients. Presentation in immunocompetent patient is even rarer. We present a case of 26-year-old female patient who presented with viral myositis secondary to hepatitis E with rhabdomyolysis with acute kidney injury with right leg foot drop due to compartment syndrome in an immunocompetent patient. Keywords: Hepatitis E, viral myositis, Rhabdomyolysis Introduction Hepatitis E is one of a rare cause of viral myositis in immunocompromised patients. The clinical manifestations ranges from myalgias to rhabdomyolysis with myoglobinuric renal failure. Here, we present a case of viral myositis with rhabdomyolysis and acute kidney injury secondary to acute hepatitis E infection in immunocompetent patient.